Anomalous conductivity tensor in the Dirac semimetal Na3Bi. (11th May 2016) - Xiong, Jun; Kushwaha, Satya; Krizan, Jason; Liang, Tian; Cava, R. J.; Ong, N. P.
Abstract: Na3 Bi is a Dirac semimetal with protected nodes that may be sensitive to the breaking of time-reversal invariance in a magnetic field B . We report experiments which reveal that both the conductivity and resistivity tensors exhibit robust anomalies in B . The resistivity is B -linear up to 35 T, while the Hall angle exhibits an unusual profile approaching a step function. The conductivities and share identical power-law dependences at large B . We propose that these significant deviations from conventional transport result from an unusual sensitivity of the transport lifetime to B . The transport features are compared with those in Cd3 As2 .